2017
DOI: 10.1089/omi.2017.0128
|View full text |Cite
|
Sign up to set email alerts
|

Time for Multiple Extraction Methods in Proteomics? A Comparison of Three Protein Extraction Methods in the Eustigmatophyte AlgaMicrochloropsis gaditanaCCMP526

Abstract: Proteomics is a crucial postgenomic biotechnology for functional and systems scale analyses in cell and integrative biology, not to mention clinical and precision medicine research. However, a fundamental requirement for an accurate examination of the protein complement of cells is an efficient method for extracting the proteins. This study reports on the evaluation of three protein extraction methods: trichloroacetic acid (TCA)-acetone, phenol, and TRIzol, in the eustigmatophyte alga Microchloropsis gaditana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Therefore, integrating the application of different extraction methods will improve proteome coverage. Indeed, the importance of using multiple protein extraction methods to obtain comprehensive proteome coverage has been highlighted by several researchers (e.g., Karthikaichamy et al, 2017 ; Takác et al, 2017 ).…”
Section: Extraction Of Total Proteins For Comparative Proteomic Analymentioning
confidence: 99%
“…Therefore, integrating the application of different extraction methods will improve proteome coverage. Indeed, the importance of using multiple protein extraction methods to obtain comprehensive proteome coverage has been highlighted by several researchers (e.g., Karthikaichamy et al, 2017 ; Takác et al, 2017 ).…”
Section: Extraction Of Total Proteins For Comparative Proteomic Analymentioning
confidence: 99%
“…Nevertheless, it must be considered that the obtained data is highly dependent on technical and biological issues. For instance, it is known that protein extraction methods in plant proteomics can be determinant to detect hydrophobic membrane proteins and low abundant proteins (50,51). In addition, it has been reported that the use of different solid-phase extraction methods (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the increasingly recognized role of microalgae in health and disease prevention [158], the advancement of omics technologies in personalized medicine has spanned over to Eustigmatophyceae as well. They have been used in the improvement of protein extraction protocols, allowing even deeper mining of the proteomes [159,160]. This, along with the lack of toxic records from Eustigmatophyceae (e.g.…”
Section: Eustigmatophyceae For Cosmetics Medicine Pharmaceutics Andmentioning
confidence: 99%